Premature awakening and underuse of neuromuscular monitoring in a registry of patients with butyrylcholinesterase deficiency†#. (14th July 2015) - Thomsen, J. L.; Nielsen, C. V.; Palmqvist, D. F.; Gätke, M. R.
Abstract : Background: Patients with butyrylcholinesterase (BChE) deficiency can experience prolonged paralysis after receiving suxamethonium or mivacurium. We hypothesized that patients suspected of BChE deficiency had a higher risk of being awakened while paralysed and having respiratory complications if neuromuscular monitoring was not applied before awakening. Methods: We retrospectively included patients referred to the Danish Cholinesterase Research Unit between 2004 and 2012 on suspicion of BChE deficiency. We collected data on genotype, BChE activity, neuromuscular blocking agents administered, neuromuscular monitoring, and postoperative respiratory complications, defined as arterial oxygen desaturation <90%, assisted ventilation, reintubation of the trachea, and pulmonary aspiration. Patients were classified as prematurely awakened if anaesthesia had been terminated while the patient was still paralysed. Results: We included 123 patients. Neuromuscular monitoring was applied before awakening in 48 (39%) patients. A nerve stimulator was never used or only after attempted awakening in the remaining 75 (61%) patients. Premature awakening occurred in 75 (100%) and 14 (29%) of the unmonitored and monitored patients, respectively ( P <0.001, Fisher's exact test). In 11 of the monitored patients, the results of neuromuscular monitoring were interpreted as equipment failure or were disregarded. Respiratory complications occurred in 19 (25%) and five (10%) of the unmonitored and monitored patients, respectively ( P= 0.06). Conclusions: Patients with BChE deficiency are at higher risk of being awakened while paralysed if neuromuscular monitoring is not applied or used; neuromuscular monitoring is recommended whenever a neuromuscular blocking agent is administered.